The ACR/EULAR Classification Criteria for SSc - Kuznar, Wayne (MD Conference Express, 2012)
Proposed new classification criteria developed for systemic sclerosis (scleroderma; SSc) have improved sensitivity and specificity compared with the 1980 American College of Rheumatology (ACR) SSc criteria and should allow for more patients to be classified as having SSc. The proposed classification criteria are preliminary and need to be reviewed by the ACR and the European League Against Rheumatism (EULAR), but the authors do not anticipate they will be altered from the findings presented here.